2018
DOI: 10.1093/humrep/dey092
|View full text |Cite
|
Sign up to set email alerts
|

Fertility and neonatal outcomes of embryos achieving blastulation on Day 7: are they of clinical value?

Abstract: Not applicable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 34 publications
5
25
1
Order By: Relevance
“…The final inclusion was 13 studies that met the selection criteria for our meta‐analysis. Hence, 23 studies were included in the following meta‐analyses . The main characteristics and assessment for risk of bias of the included studies are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The final inclusion was 13 studies that met the selection criteria for our meta‐analysis. Hence, 23 studies were included in the following meta‐analyses . The main characteristics and assessment for risk of bias of the included studies are presented in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Hence, 23 studies were included in the following meta-analyses. 4,6,7,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The main characteristics and assessment for risk of bias of the included studies are presented in Table 1.…”
Section: Results Of the Searchesmentioning
confidence: 99%
See 1 more Smart Citation
“…Acceptable live birth rates have been obtained after Day 7 blastocyst transfers [6][7][8][9][10]. However, all of the data in these previous reports were from autologous and fresh donor oocyte IVF.…”
Section: Resultsmentioning
confidence: 99%
“…Although most human IVF laboratories culture human embryos to Day 6, an extended Day 7 culture is necessary for some patients, especially if patients have limited number of oocytes [6][7][8]. It has been reported that Day 7 blastocysts had lower implantation potential as compared with Day 5/6 blastocysts, however, transfer of Day 7 blastocysts can lead to acceptable live birth rates [9,10].…”
Section: Introductionmentioning
confidence: 99%